(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article reveals the role of mass media in the development of legal awareness and legal culture of adolescents, the content and features of positive and destructive information impact on the legal awareness of adolescents, and presents the main directions for overcoming counteraction to destructive information impact.